The good, the bad and the naive: Do fair prices signal good types or do they induce good behaviour? - Uwe Dulleck; David Johnston; Rudolf Kerschbamer; Matthias Sutter (University of Innsbruck, Research Platform Empirical and Experimental Economics (eeecon), 2012)
Evidence on behavior of experts in credence goods markets raises an important causality issue: Do fair prices induce good behavior, or do good experts post fair prices? To answer this question we propose and test a model with three seller types: the good choose fair prices and behave consumer-friendly; the bad mimic the good types price-setting, but cheat on quality; and the naive fall victim to a projection bias that all sellers behave like the bad types. OLS, sample selection and fixed effects regressions support the models predictions and show that causality goes from good experts to fair prices.
Keywords: C91; L15; D82; D40; 330; credence goods; experts; pricing; experiment; other regarding preferences; signalling; projection bias